Assessment of miR-212 and Other Biomarkers in the Diagnosis and Treatment of HBV-infection-related Liver Diseases - Zhang, Yigan; Xi, Huaze; Nie, Xin; Zhang, Peng; Lan, Ning; Lu, Ying; Liu, Jinrong; Yuan, Wenzhen (Current Drug Metabolism, 2019)
Objectives: Our study aims to detect the sensitivity of the new biomarker miR-212 existing in serum exosomes along with other hepatocellular carcinoma biomarkers such as AFP (alpha-fetoprotein), CA125 (carbohydrate antigen-ca125), and Hbx protein in the diagnosis of HBV-related liver diseases. We also aim to study the roles of these biomarkers in the progression of chronic hepatitis B and provide scientific data to show the clinical value of these biomarkers. Methods: We selected 200 patients with HBV-infection (58 cases of chronic hepatitis B, 47 cases of hepatocellular carcinoma, 30 cases of compensatory phase cirrhosis, and 65 cases of decompensatory phase cirrhosis), 31 patients with primary liver cancer without HBV infection, and 70 healthy individuals as the control group. The expression level of serum AFP and CA125 was detected with electrochemiluminescence immunoassay. The expression level of the Hbx protein was detected with ELISA. Meanwhile, the expression level of miR-212 in serum was analyzed with RT-qPCR. We collected patients’ clinical information following the Child-Pugh classification and MELD score criterion, and statistical analysis was made between the expression level of miR-212 and the collected clinical indexes. Lastly, we predicted the target genes of the miR-212 and its functions using bioinformatics methods such as cluster analysis and survival prediction. Results: Compared to the control group, the expression level of miR-212 in HBV infected patients was remarkably increased (P<0.05), especially between the HBV-infection Hepatocellular carcinoma group and the non-HBVinfection liver cancer group (P<0.05). The expression of miR-212 was increased in patients’ Child-Pugh classification, MELD score, and TNM staging. Moreover, the sensitivity and specificity of miR-212 were superior to AFP, CA125, and HBx protein. Conclusion: There is a linear relationship between disease progression and expression level of miR-212 in the serum of HBV infected patients. This demonstrates that miR-212 plays a significant role in liver diseases. miR-212 is expected to be a new biomarker used for the diagnosis and assessment of patients with HBV-infection-related liver diseases.
Keywords: hepatocellular carcinoma